Love and Compassion in Learning: A Qur'an and Hadith Perspective in the Context of Inclusive Education - Rita Sriayu; Mahyuddin Barni; Abd. Majid; Iskandar (The Islamic Education and Multiculturalism Foundation, 2026)
This research aims to analyze the concepts of vinta (mahabbah) and compassion (rahmah) from the perspective of the Quran and hadith, and their relevance to inclusive education practices in Islam. This study is based on the understanding that love and compassion are the essence of Islamic teachings, which are not only normatively taught in religious texts but also have significant implications for a learning process that is friendly, just, and respectful of diversity. The research method used is literature review, examining literature related to the Quran, Hadith, Islamic education, and inclusive education. The study results show that the Quran and Hadith clearly emphasize the importance of rahmah and mahabbah as the foundation for social and educational relationships. These values then became the basic principles of inclusive education in Islam, as they encourage an attitude of valuing differences, empathy, and providing equal learning opportunities for all students. In addition, the application of love and affection in inclusive learning can be realized thru teacher modeling, a humanistic approach, teaching strategies responsive to individual needs, and the creation of a safe and supportive school culture. Thus, this research confirms that integrating the values of love and compassion is an important foundation for realizing holistic, humanistic, and inclusive education that aligns with the principles of Islamic education.